Evaluating Factors Impacting Medication Adherence Among Rural, Urban, and Suburban Populations. Issue 4 (10th January 2018) - Arbuckle, Cody; Tomaszewski, Daniel; Aronson, Benjamin D.; Brown, Lawrence; Schommer, Jon; Morisky, Donald; Linstead, Erik
Abstract: Purpose: To evaluate differences in prescription medication adherence rates, as well as influencing factors, in rural and urban adults. Methods: This is a retrospective analysis of the 2015 National Consumer Survey on the Medication Experience and Pharmacists' Role. A total of 26, 173 participants completed the survey and provided usable data. Participants using between 1 and 30 prescription medications and living more than 0 miles and up to 200 miles from their nearest pharmacy were selected for the study, resulting in a total of 15, 933 participants. Data from the 2010 US Census and Rural Health Research Center were used to determine the population density of each participant's ZIP code. Participant adherence to reported chronic medications was measured based on the 8‐item Morisky Medication Adherence Scale (MMAS‐8). Findings: Overall adherence rates did not differ significantly between rural and urban adults with average adherence based on MMAS‐8 scores of 5.58 and 5.64, respectively ( P = .253). Age, income, education, male sex, and white race/ethnicity were associated with higher adherence rates. While the overall adherence rates between urban and rural adults were not significantly different, the factors that influenced adherence varied between age‐specific population density groupings. Conclusion: These analyses suggest that there is no significant difference in adherence between rural and urban populations; however, the factors contributing to medication adherence may vary based on age and population density. Future adherence intervention methods should be designed with consideration for these individualized factors.